2021
DOI: 10.1111/rec.13521
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation and structure change when producing and using mixed‐source seed lots for restoration

Abstract: Large-scale ecological restoration efforts increasingly require large quantities of genetically diverse seeds adapted to a range of potential sites. To meet this demand, there is a growing emphasis on mixing multiple, regionally sourced source populations in production settings to produce large quantities of genetically diverse seeds. However, because few empirical studies are available, it is unclear how source population representation and genetic diversity shift through production and restoration use of mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Higher gene diversity may provide a higher chance of evolution during cultivation. For example, the contribution of individual source populations to the gene pool of the seed lot can shift during the propagation process (Kucera et al, 2022; St. Clair et al, 2020). The observed stronger differentiation across generations in the material of Producer 1 is thus potentially caused by the more diverse starting material.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher gene diversity may provide a higher chance of evolution during cultivation. For example, the contribution of individual source populations to the gene pool of the seed lot can shift during the propagation process (Kucera et al, 2022; St. Clair et al, 2020). The observed stronger differentiation across generations in the material of Producer 1 is thus potentially caused by the more diverse starting material.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies documented evolutionary changes in ex situ cultivation in botanical gardens (Ensslin & Godefroid, 2019; Rauschkolb et al, 2019), but ex situ populations are usually very small, whereas the cultivation of plants for ecosystem restoration usually involves much larger populations. The few studies that focused specifically on the evolution of plants for ecological restoration worked with individual species and/or documented cultivation only across a single generation (Dyer et al, 2016; Kucera et al, 2022; Pizza et al, 2021; St. Clair et al, 2020). Only one previous study focused on multiple cultivation generations across multiple species, and it found rather minor cultivation effects which differed between species (Nagel et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…While the unintentional loss of genetic diversity through propagation has been a longstanding concern of restoration ecologists (Basey et al., 2015; Espeland et al., 2017; Havens et al., 2004), most studies have documented genetic shifts rather than decreases in genetic diversity (Dyer et al., 2016; Nagel et al., 2019; St. Clair et al., 2020). On the other hand, large scale seed production for restoration has not led to major changes in genetic diversity in other studied species (Kucera et al., 2022; St. Clair et al., 2020), even in those that experience dormancy (Conrady et al., 2022). In some cases, propagation practices can lead to ex situ populations harboring greater levels of genetic diversity compared to in situ populations (Conrady et al., 2022; St. Clair et al., 2020), demonstrating that cultivation, when applied appropriately, can benefit species that are to be restored in harsh in situ conditions (Chivers et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Clair et al, 2020). On the other hand, large scale seed production for restoration has not led to major changes in genetic diversity in other studied species (Kucera et al, 2022;St. Clair et al, 2020), even in those that experience dormancy (Conrady et al, 2022).…”
mentioning
confidence: 99%
“…The potential evolution of wild plants during cultivation for ecological restoration has been intensely debated, but experimental evidence is scarce and inconclusive (10,11). Some previous studies used molecular markers to understand genetic drift during the seed production (18,19), yet none of these focused on adaptive genetic variation and thus, were unable to test for selection (20). Common garden studies that tested for heritable phenotypic changes were so far limited to individual species, only one cultivated generation, or they lacked adequate comparisons to the wild ancestors (21)(22)(23), and the obtained results vary.…”
Section: Introductionmentioning
confidence: 99%